A tri-band terrestrial beacon digital receiver system for TEC measurements - Zhang, Chu-Yuan; Zhao, Rong-Bing; Zhang, Dong; Yu, Dong-Mei; Wu, Ya-Jun; Shang-Guan, Wei-Hua; Yan, Zhen (Frontiers in Astronomy and Space Sciences, 2023)
The ionosphere is an important component of near-Earth space that has a significant impact on communication and navigation. Furthermore, the total electron content of the ionosphere (TEC) is a widely used parameter in near Earth plasma environment studies. A design of a digital beacon receiver system for automatically measuring TEC is presented. Universal Software Radio Peripheral (Usrp) hardware equipment with software-defined radio technology was used in tri-band beacon digital receiver to receive and rapidly pre-process beacon signals from satellites in different frequency bands. A software system is built to implement the automatic control of the receiver and to enable data processing of the pre-processed data in order to obtain its phase information and derive the TEC. The tri-band digital beacon receiver system is experimentally proven to automatically detect and archive transit satellites in real time, automatically receive and process satellite beacon signals with recording, and automatically generate TEC measurement results.